2022
DOI: 10.3390/su142416941
|View full text |Cite
|
Sign up to set email alerts
|

Pochonia chlamydosporia Is the Most Prevalent Fungal Species Responsible for Meloidogyne Suppression in Sustainable Vegetable Production Systems

Abstract: The fluctuations in Meloidogyne densities and fungal egg parasitism were determined from February 2015 to July 2016 in four vegetable production sites conducted under organic production and two sides conducted under integrated standards. At each site, the soil nematode densities at transplanting and at the end of the crops, the galling index, the number of eggs in roots, and the percentage of fungal egg parasitism were determined, and the fungal species were identified. In addition, two pot experiments were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Moreover, its liquid culture is simple and cost-effective (Uthoff et al, 2024 ). Ghahremani et al had reported that P. chlamydosporia is the common antagonistic fungus of vegetable root-node nematodes (Ghahremani et al, 2022 ). Zavala et al ( 2017 ) discovered that P. chlamydosporia not only controls nematode diseases but also promotes the growth of plants, it was found that P. chlamydosporia promoted plant growth and improved the yield through the jasmonate signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its liquid culture is simple and cost-effective (Uthoff et al, 2024 ). Ghahremani et al had reported that P. chlamydosporia is the common antagonistic fungus of vegetable root-node nematodes (Ghahremani et al, 2022 ). Zavala et al ( 2017 ) discovered that P. chlamydosporia not only controls nematode diseases but also promotes the growth of plants, it was found that P. chlamydosporia promoted plant growth and improved the yield through the jasmonate signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the putative nematode antagonist community detected in the Vredepeel experimental field comprised antagonists whose presence could be anticipated, and it was supplemented with a range of taxa that we did not foresee to be present in this experimental field. An exception is the fungus Pochonia chlamydosporia which was not found in our experimental field, although being the most abundant and widespread naturally occurring egg-parasite of Meloidogyne in organic and integrated vegetable production systems (Giné et al, 2013;Ghahremani et al, 2022).…”
Section: Discussionmentioning
confidence: 78%